Using of the Robotic Operating System for PID control education. Issue 29 (2015) - Beschi, Manuel; Adamini, Riccardo; Marini, Alberto; Visioli, Antonio
Abstract: The paper deals with the use of the Robotic-Operating-System (ROS) as an educational tool for control engineering students. This software suite, in fact, simplifies the required communication effort in distributed systems over networks helping the development of learning tools in both robotic and control fields. In particular, we present a tool which allows the user to understand the tuning and the behaviour of proportional-integral-derivative (PID) controllers when they are used to control first-order-plus-dead systems in distributed networks.